Rotating electrical machines and power systems - Patrick, Dale R (Fairmont press, 1997)
Now available in its fully updated second edition, this authoritative reference will serve as your complete guide to today's rotating electrical machinery and power systems, presented in a clear, easy-to-assimilate format. The authors have developed an "electrical power systems" model to present key concepts of production, distribution, conversion and control systems. Within this model the key subsystems are then explored in detail. Subjects covered include physical characteristics of rotating systems, electrical power basics, AC and DC generators, transformers, power distribution systems, DC motors, single-phase and three-phase AC motors, specialized electrical machinery, control systems, and measurement and testing